Compositional controls on nanopore structure in different shale lithofacies: A comparison with pure clays and isolated kerogens - Yuan, Yujie; Rezaee, Reza; Yu, Hongyan; Zou, J.; Liu, K.; Zhang, Y. (2021)
Nanopore structure development in shale is intimated with lithofacies that demonstrates a large variety in different formations. It is critical to differentiate and quantify the separate impact of lithological components (minerals and organic matter (OM)) on pore structure attributes associated with shale gas storage capacity. In this study, we classified shales into 12 lithofacies for compositional and petrophysical quantification. Parameters of our main target, the Goldwyer shales (argillaceous OM-poor, argillaceous OM-moderate, and argillaceous OM-rich lithofacies) were further compared with other shale lithofacies, pure clays and isolated kerogens, using XRD, Rock-Eval pyrolysis, Ar-SEM and low-pressure CO2/N2 gas adsorption techniques. Results show that argillaceous OM-rich lithofacies (TOC > 2% and illite-dominated clay contents > 50%) develop more interconnected pores with better hydrocarbon storage potential. The argillaceous lithofacies have large amounts of cleavage-sheet pores with large pore volumes; the accumulative pore volume of the pores in diameter from 2 to 17 nm constitutes the major amount of total pore volume that is associated with free gas. The OM-rich lithofacies develop more OM-pores (particularly in pore diameter <2 nm) that contain extraordinarily high specific surface area (SSA); the SSA of micropores makes up the major total surface area that is intimated with adsorbed gas. Further investigation on pure clays and isolated kerogens clarifies that illite mainly controls the pore sizes from 2 to 17 nm, resulting in large pore volumes in argillaceous shales. By contrast, isolated kerogen dominantly controls micropores in diameter <2 nm, leading to a larger surface area with higher adsorbed gas storage in organic-rich shales.